An analysis of the distribution and spectrum of alpha thalassemia mutations in Rasht City, North of Iran - Asghari Ahmadabad, Mona; Pourreza, Noushin; Ramezanpour, Setareh; Baghersalimi, Adel; Enshaei, Mersedeh; Askari, Marjan; Alizadeh, Amirhossein; Izadi, Elahe; Darbandi, Bahram (Frontiers in Pediatrics, 2023)
Background: Alpha thalassemia is one of the most common hereditary hemoglobin disorders worldwide, particularly in the Middle East, including Iran. Therefore, determining the spectrum and distribution of alpha thalassemia mutation is a fundamental component of preventive approaches and management strategies. Methods: The present study reviewed the genetic testing and blood laboratory results of 455 marriage candidates who were suspected of being thalassemia carriers and performed genetic testing from March 21, 2013, to December 31, 2020, in Rasht City. Results: A total of 114 (25.05%) alpha thalassemia cases were identified. Fifteen different alpha mutations were found. The most common mutation among the study population was -α3.7 deletion in 55 cases (48.24%), followed by Hb Constant Spring (C.S) with 21 patients (18.42%) and poly A2 with 16 patients (14.03%). Also, most of the patients were silent carriers. The deletion type of mutation was much more common than non-deletion mutations. Conclusion: Our study reveals genetic heterogeneity and alpha thalassemia diversity among Rasht City populations. We expect that these findings will help guide premarital screening and genetic counseling, prenatal diagnosis of thalassemia, preventive strategy development, as well as completion of the Alpha Thalassemia catalog in Guilan province.